PERAN KOMITE SEKOLAH DALAM MENDUKUNG MANAJEMEN BERBASIS SEKOLAH DI SD - Ananda, Rizki; Kurniawan, Heri; Syahri Jasmi , Elvi; Rafid Alfarizi , Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of school committees in supporting the implementation of school-based management in elementary schools (SD). The study used a qualitative descriptive method with a Systematic Literature Review (SLR) approach through a review of various journals, scientific articles, and relevant sources related to school committees and school-based management. Data were collected through a process of identification, selection, analysis, and synthesis of literature relevant to the research topic. The results of the study indicate that school committees play a crucial role as advisors, supporters, controllers, and liaisons between schools and the community. The existence of school committees can assist schools in program development, supervision of educational activities, improvement of facilities and infrastructure, and support the creation of transparency and accountability in school management. In addition, good cooperation between school committees and schools can increase the effectiveness of school-based management implementation, thus improving the quality of education in elementary schools and optimally achieving educational goals.